2017
DOI: 10.1111/jam.13627
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial aryl-crowned polyketide from Bacillus subtilis associated with seaweed Anthophycus longifolius

Abstract: Aims: Microbiological, biotechnological and chemical characterization of a previously undescribed aryl-crowned polyketide from Bacillus subtilis MTCC 10403 isolated from brown seaweed Anthophycus longifolius with activity against opportunistic Gram-negative food-borne pathogenic bacterial strains. Methods and Results: A culture-dependent method was used to isolate heterotrophic B. subtilis associated with A. longifolius and assessed for its antimicrobial properties. Minimum inhibitory concentration (MIC) of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(19 citation statements)
references
References 35 publications
1
18
0
Order By: Relevance
“…In contrast, only four were detected in strain E681, as the genes or gene clusters for tridecaptin and kalimantacin synthesis were absent. Among the six antibiotics, polymyxin, tridecaptin, and polyketide are able to suppress G - bacteria ( Cochrane et al, 2015 ; Chakraborty et al, 2018 ; Gounani et al, 2018 ), whereas mersacidin, kalimantacin, and bacitracin show activity against G + bacteria ( Konzl et al, 1997 ; Sahl and Bierbaum, 1998 ; Thistlethwaite et al, 2017 ). The identities of the genes or gene clusters related to the six antibiotics were clearly higher between strains HY96-2 and SC2 than between strains HY96-2 and E681.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, only four were detected in strain E681, as the genes or gene clusters for tridecaptin and kalimantacin synthesis were absent. Among the six antibiotics, polymyxin, tridecaptin, and polyketide are able to suppress G - bacteria ( Cochrane et al, 2015 ; Chakraborty et al, 2018 ; Gounani et al, 2018 ), whereas mersacidin, kalimantacin, and bacitracin show activity against G + bacteria ( Konzl et al, 1997 ; Sahl and Bierbaum, 1998 ; Thistlethwaite et al, 2017 ). The identities of the genes or gene clusters related to the six antibiotics were clearly higher between strains HY96-2 and SC2 than between strains HY96-2 and E681.…”
Section: Discussionmentioning
confidence: 99%
“…Various researches were focused on the antifouling and antibiotic activities of macroalgae-associated bacterial species (Zheng et al 2005;Kanagasabhapathy et al 2008;Penesyan et al 2009;Wiese et al 2009;Chakraborty et al 2018). In 1997, Imamura et al reported the production of a phenazine compound with antimicrobial activity, by a strain of Pelagiobacter variabilis isolated from the brown marine macroalgae Pocockiella variegata.…”
Section: Introductionmentioning
confidence: 99%
“…Compared with 1, 7, 37 and 7-O-malonyl macrolactin A (MMA, 16), 38 exhibited greater anti-inflammatory activity owing to the existence of the epoxy ring. Further analysis revealed that 38 could (Chakraborty et al 2014(Chakraborty et al , 2017Gustafson et al 1989;Jaruchoktaweechai et al 2000;Ji et al 2010;Lu et al 2008;Mohamad et al 2012;Mondol et al 2011b;Muhammad and Hee 2014;Nagao et al 2001;Schneider et al 2007;Tareq et al 2013;Xue et al 2008;Yan et al 2016;Yoo et al 2006;Zheng et al 2007) significantly inhibit the mRNA expression of inducible nitric oxide synthase (iNOS), interleukin-1β (IL-1β) and interleukin-6 (IL-6), which are important targets in the treatment of inflammatory diseases.…”
Section: -O-2′e-butenoyl Macrolactin a (37)mentioning
confidence: 99%
“…The antimicrobial mode of 39 was found to be iron chelating similar to siderophores. It was proposed that the side chain 6-(2-acetylphenyl)-5-hydroxyhexanoate moiety and pentane-2,4-diol moiety of the lactone ring might potentially bind freely available Fe 3+ , resulting in inadequacy of the essential elements required for multiplication of pathogens (Chakraborty et al 2017).…”
Section: -O-6′-(2″-acetylphenyl)-5′-hydroxyhexanoate Macrolactin (39)mentioning
confidence: 99%
See 1 more Smart Citation